2019
DOI: 10.1017/s1047951119002154
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in infants and children in the Western Cape, South Africa: a retrospective analysis

Abstract: Infective endocarditis is a microbial infection of the endothelial surface of the heart, predominantly the heart valves, that is associated with high mortality and morbidity. Few contemporary data exist regarding affected children in our context.Aims and Objectives:We aimed to describe the profile and treatment outcomes of infant and childhood endocarditis at our facilities.Methods:This is a retrospective analysis of infants and children with endocarditis at two public sector hospitals in the Western Cape Prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Gram-positive cocci were the most common cause of IE in our study; however, the composition of pathogenic microorganisms differed signi cantly according to HD status. S. aureus was more common in non-HD patients with IE, consistent with some studies [19][20][21], and Streptococcus was most common in HD patients, as other studies showed [1]. In other studies, the frequency of S. aureus and Streptococcus was similar [22].…”
Section: Discussionsupporting
confidence: 86%
“…Gram-positive cocci were the most common cause of IE in our study; however, the composition of pathogenic microorganisms differed signi cantly according to HD status. S. aureus was more common in non-HD patients with IE, consistent with some studies [19][20][21], and Streptococcus was most common in HD patients, as other studies showed [1]. In other studies, the frequency of S. aureus and Streptococcus was similar [22].…”
Section: Discussionsupporting
confidence: 86%
“…Outcome data were reported in 23 (55%) of 42 studies. [21][22][23][25][26][27][28][29][31][32][33]35,[40][41][42][45][46][47][48][49][50][51][52] The pooled in-hospital mortality rate across studies was 22•6% (95% CI 19•5-25•9), which was similar in studies from north Africa (22•5%) and those from sub-Saharan Africa (22•7%; figure 4). Heart failure was the most frequent complication, occurring in 47 5 and the appendix (pp 62-66).…”
Section: Resultsmentioning
confidence: 85%
“…22,[29][30][31]36,38,43 A microorganism was detected in 48 Twelve (29%) of 42 studies reported data for surgical treatment of infective endo carditis. [21][22][23]25,26,28,29,31,40,42,45,52 The rate of surgery uptake in studies from north Africa was 49•7% (95% CI 42•5-56•9), ranging from 30•2% to 64•6%, whereas the rate of surgery uptake in two studies from sub-Saharan Africa was 46•1% (39•0-53•4). The pooled rate of surgical treatment of infective endocarditis was 49•1% (95% CI 43•2-55•1; appendix p 56).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This study aimed to identify diagnosis, management and short outcome of IE at Ahmed Gasim Children's hospital; during the study period, 6260 patients were admitted,47 patients were identified to have IE according to Dukes criteria.Three patients fulfilled the criteria for Definite endocarditis and 44 were classified as Possible; 6 IE admission rate was 7.5: 1000 admission, this figure is high compared to other countries even in Africa, 8 a large multicentre study from USA from 2003 to 2010showed the annual incidence rate in the United States was 0.05-0.12 cases per 1000 paediatric admissions, 1 CHD has been associated with increased risk of periodontal infection and this in turn increased the risk of endocarditis in CHD cases. Previous studies from Ahmed Gasim hospital showed that Sudanese children with CHD are at increased risk of severe gingivitis and caries compared to the children without CHD.…”
Section: Discussionmentioning
confidence: 85%